Inequality & violence in the United States: casualties of capitalism - Chasin, Barbara H. (Lexington Books, 2023)
"While mass shootings make headlines, the more routine effects of corporate and government decisions on our well-being are downplayed. This book analyzes how economic and political inequalities lead to forms of violence that routinely cause harm"--